2022
DOI: 10.3389/fneur.2022.935459
|View full text |Cite
|
Sign up to set email alerts
|

Use of 18F-FDG-PET/CT in differential diagnosis of primary central nervous system lymphoma and high-grade gliomas: A meta-analysis

Abstract: BackgroundPrimary central nervous system lymphoma (PCNSL) and high-grade glioma (HGG) appear similar under imaging. However, since the two tumors vary in their treatment methods, their differential diagnosis is crucial. The use of 18F-fluorodeoxyglucose positron emission tomography computed tomography (18F-FDG-PET/CT) imaging to effectively distinguish between the two tumors is not clear; therefore, a meta-analysis was carried out to determine its effectiveness.Materials and methodsThe databases PubMed, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[ 6 ] PET is widely used as a functional imaging modality applying radiotracers such as 11 C-Methionine and 18 F-FDG. [ 14 ] We have previously reported that the TNR of 2.4 from 18 F-FDG-PET was consistent with the pathological diagnosis of PCNSL, with this method offering 83.8% sensitivity and 95.2% specificity. [ 6 ] Conversely, the TNR from met-PET was very high for PCNSL but not significantly different from that for glioblastoma (GBM).…”
Section: Discussionmentioning
confidence: 61%
“…[ 6 ] PET is widely used as a functional imaging modality applying radiotracers such as 11 C-Methionine and 18 F-FDG. [ 14 ] We have previously reported that the TNR of 2.4 from 18 F-FDG-PET was consistent with the pathological diagnosis of PCNSL, with this method offering 83.8% sensitivity and 95.2% specificity. [ 6 ] Conversely, the TNR from met-PET was very high for PCNSL but not significantly different from that for glioblastoma (GBM).…”
Section: Discussionmentioning
confidence: 61%
“…Combined with MRI, PET, especially if carried out with radiolabeled amino acids, is acquiring an increasingly relevant role in the distinction between HGG and PCNSL [141], HGG and metastases [142,143] and HGG and therapy-related damage [144,145].…”
Section: Modelling the Diagnosis Of Hggmentioning
confidence: 99%